Pra-Natal Education in Tarbawi Interpretation - Nur Wahid, Muhammad Gus; Mulyadi, Mulyadi; Mustofa, Lutfi; Barizi, Ahmad (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Prenatal education can be understood as a conscious effort by prospective parents, especially mothers, to guide and educate the fetus until it is born, with the aim of creating a good personality such as emotional intelligence and intelligence. Islamic teachings state that the pregnancy (prenatal) period is the determining period for a child's future life. The aim of this research is to analyze the importance of prenatal education from Tarbawi's perspective. The method used is a qualitative descriptive method, using library research or a literature review. Data collection techniques include identifying discourses, journals, articles, and books related to the research title and analyzing data using content analysis. The research results show that it is important for prospective babies to receive care from both parents, especially from the mother, in the form of Islamic amulets given through activities such as devotions, reading the Koran, listening to prayers, and so on. and get adequate nutrition.